«ШӘРИЯР» ДӘСТАНЫНДА ҲУҚЫҚЫЙ ТӘЛИМ ҲӘМ ТӘРБИЯ МӘСЕЛЕЛЕРИ - Алламбергенов, Е.К. (ILIM hám JÁMIYET, 2020)
The author of the article studies the issues of law, kuping law demands using law in practice, negative relation to words breakers of law in the epos «Shariyar», the issues of legal education on the materials of the epos.